Small and Medium Scale Enterprises and Economic Performance in Nigeria: A Case of Chicken Republic Fast Food in Ekiti State: Array - Ologbenla, Patrick (Acta Universitatis Danubius. Œconomica, 2021)
The study examined the contributions of the SMEs to the Nigerian economic performance through the food and beverage industry and using the Chicken Republic eateries in Ekiti State, Nigeria as a case study. The study used a survey method by collecting primary data from the target respondents through structured questionnaire. The results were analyzed using both descriptive and inferential statistics. The results indicate that SMEs contribute to the Nigeria economic performance via employment and job creation, income and output/services provision, promotion of innovation and entrepreneurship, infrastructural and community development , contribution to macroeconomic policy. The findings for the analysis indicate that employment and job creation, income and output generation, promotion of innovation and entrepreneurship are the main areas where SMEs contribute to the economic performance of Nigeria. It was discovered from the results that SMEs are not include as ti should be in macroeconomic policy of the government. In addition, it was also found out the provision of infrastructure and community developments are to be left for the government and not the SMEs.